Latino High School Graduation Defying the Odds - Romo, Harriett D. (University of Texas Press, 2021)
While high school drop-out rates have steadily declined among white and African American students over the last twenty years, a constant 35 percent of Latino students continue to quit school before graduation. In this pioneering work, Harriett Romo and Toni Falbo reveal how a group of at-risk Latino students defied the odds and earned a high school diploma. Romo and Falbo tracked the progress of 100 students in Austin, Texas, from 1989 to 1993. Drawing on interviews with the students and their parents, school records, and fieldwork in the schools and communities, the authors identify both the obstacles that caused many students to drop out and the successful strategies that other students and their parents pursued to ensure high school graduation. The authors conclude with seven far-reaching recommendations for changes in the public schools. Sure to provoke debate among all school constituencies, this book will be required reading for school administrators, teachers, parents, legislators, and community leaders
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Nov 2021)
Keywords: SOCIAL SCIENCE / Ethnic Studies / General; High school dropouts -- United States -- Case studies; High school graduates -- United States -- Case studies; Mexican American students -- Social conditions -- Case studies; Youth with social disabilities -- Education (Secondary) -- United States -- Case studies